2008
DOI: 10.1038/onc.2008.103
|View full text |Cite
|
Sign up to set email alerts
|

Mycoplasma infection suppresses p53, activates NF-κB and cooperates with oncogenic Ras in rodent fibroblast transformation

Abstract: Prokaryotes of the genus Mycoplasma are the smallest cellular organisms that persist as obligate extracellular parasites. Although mycoplasma infection is known to be associated with chromosomal instability and can promote malignant transformation, the mechanisms underlying these phenomena remain unknown. Since persistence of many cellular parasites requires suppression of apoptosis in host cells, we tested the effect of mycoplasma infection on the activity of the p53 and nuclear factor (NF)-jB pathways, major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(80 citation statements)
references
References 33 publications
6
72
1
1
Order By: Relevance
“…This cell line has an undetectable background level of spontaneous transformation and has been shown to undergo senescence-like growth arrest in response to H-Ras V12 expression similar to MEFs (26,30). In addition, like MEFs, REF52 cells lacking p53 activity undergo transformation upon H-Ras V12 expression, which we confirmed using shRNA-mediated knockdown of p53 expression (26).…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…This cell line has an undetectable background level of spontaneous transformation and has been shown to undergo senescence-like growth arrest in response to H-Ras V12 expression similar to MEFs (26,30). In addition, like MEFs, REF52 cells lacking p53 activity undergo transformation upon H-Ras V12 expression, which we confirmed using shRNA-mediated knockdown of p53 expression (26).…”
Section: Resultssupporting
confidence: 55%
“…In this regard, NASPs resemble genetic suppressor elements described in our earlier work that encode fragments of p53 protein that act as dominantnegative p53 mutants also capable of cooperation with Ras (27). Even more relevant is our recent work on the association of mycoplasma infection with cancer predisposition where we found that the chronic, typically asymptomatic infections established by this class of bacteria lead to activation of NF-κB, suppression of p53, and promotion of oncogenic Ras-induced malignant transformation (30). Thus, sustained NF-κB activation resulting from infectious agents (such as mycoplasma) might promote cancer development not only through known NF-κB-induced factors (e.g., antiapoptotic factors and growth-promoting cytokines), but also through suppression of p53, which could impact multiple pathways of tumorigenesis, including sensitivity to oncogeneinduced transformation.…”
Section: Discussionmentioning
confidence: 90%
“…These observations indicate that mycoplasma infection plays the role of a p53-suppressing oncogene that cooperates with Ras in cell transformation and suggest that the carcinogenic and mutagenic effects of mycoplasma might be due to NF-κB-mediated inhibition of p53. 65 The observed ability of mycoplasma infection to cooperate with a dominant oncogene in cell transformation is likely to be more than just a laboratory phenomenon. Inspired by our in vitro findings, we recently undertook a clinical study in which we looked at the presence of mycoplasma in the prostates of men suspected of having prostate cancer due to elevated prostate-specific antigen (PSA) levels.…”
Section: Nf-κb Against P53: a Double-edged Swordmentioning
confidence: 99%
“…In some cases, mycoplasmas have been shown to induce the production of proteins that play essential roles in the development of malignancy. Examples are the mycoplasmal-promoted production in diverse types of cultured cells of bone morphogenetic protein 2 (BMP2) that enhances tumor growth by increasing cell proliferation [73]; mycoplasma-induced diminished activation of the tumor suppression protein p53, and enhanced fibroblast transformation by the oncogenic H-ras [74] ; promotion of cancer cell motility and migration by P37, the major immunogen of M. hyorhinis, through activation of the matrix metalloproteinase-2 [75].…”
Section: Transformation Of Cells Mediated By Mycoplasmasmentioning
confidence: 99%
“…The interaction with the receptors triggers cascades of cellular signals within the cell, and the complex pathways culminate in a variety of host cell responses. Mycoplasmas and mycoplasmal LPP are known to activate the transcription factors NF-B [74,79] and AP-1 [1 4], via TLRdownstream cascades involving kinases (MAPKKKs-IKKs and MAPKKKs-MAPKKsMAPKs). Known mycoplasma-affected target genes are mainly those responsible for proinflammatory proteins [4], and those involved in malignant cell transformation [72], with little information available on genes responsible for other proteins [53,79,80,81].…”
Section: Signal Transduction Pathwaysmentioning
confidence: 99%